Current Trends in the Teaching of Political Economy (UNWE Yearbook, 2015)
After 1989 it was created a false impression of political economy as a discipline associated unilaterally with the state socialism and its Marxist-Leninist political economy. Accordingly, the teaching of this discipline was discontinued and it was replaced by macro and microeconomics, which were seen as ideologically neutral and consistent with the realities of the market economy. It is shown on the background of development of political economy in the developed western countries in the last two decades the inadequacy of the imposed notions of political economy in our country. This discipline is now undergoing a renaissance in many different schools and paradigms. It is taught and studied in all major universities in the world. It is especially investigated the place of this discipline at Harvard University and London School of Economics and Political Science. A study is made also of the most important publications in recent years in the field of political economy, various specialized journals on political economy and on this basis its main problem fields are defined.